1999
DOI: 10.1006/jmsc.1999.0604
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton distribution in the western and eastern Black Sea in spring and autumn 1995

Abstract: Species composition, abundance, and biomass of micro-(>15 m) and nano-(<15 m) phytoplankton were studied in the western and eastern Black Sea during March-April and October 1995. A total of 142 species were identified, of which >50% were dinoflagellates. Abundance and biomass values were lower during the March-April period (average 129 28 thousand cells l 1 and 330 124 g l 1) than during the October period (average 364 161 thousand cells l 1 and 1794 515 g l 1) and compared with previous investigations. Values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 15 publications
(24 reference statements)
1
21
1
Order By: Relevance
“…Phytoplankton samples were preserved immediately in 1% Lugol solution. A sedimentation method was used for taxonomic identification and algal cell counting [27,28]. Phytoplankton was identified and counted using a Sedgwick-Rafter chamber with the standard light microscope (OLYMPUS C41); before counting, the whole sample was gently mixed.…”
Section: ) Samplingmentioning
confidence: 99%
“…Phytoplankton samples were preserved immediately in 1% Lugol solution. A sedimentation method was used for taxonomic identification and algal cell counting [27,28]. Phytoplankton was identified and counted using a Sedgwick-Rafter chamber with the standard light microscope (OLYMPUS C41); before counting, the whole sample was gently mixed.…”
Section: ) Samplingmentioning
confidence: 99%
“…A sedimentation method was used for taxon identification and counting (Zhang and Huang, 1991;Eker et al, 1999). Phytoplankton was counted with a standard light microscope (OLYMPUS C41).…”
Section: Qualitative and Quantitative Investigation Of Phytoplanktonmentioning
confidence: 99%
“…This might be due to the multifactoral interactions of phytoplankton communities and the non-linearity of the responses. Previous studies showed that small-sized microphytoplankton species were dominant in the studied area (Eker et al, 1999;Eker and Kıdeys, 2003). This may be attributed to the presence of small cells having problems of microscopic identification and to the difficulty in determination of their biomass (Llewellyn at al 2005).…”
Section: Discussionmentioning
confidence: 71%